2011
DOI: 10.1007/s11999-011-1780-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Osteoporosis and Fractures

Abstract: Background Osteoporosis is generally thought of as a ''woman's disease'' because the prevalence of osteoporosis and the rate of fractures are much higher in postmenopausal women than in older men. However, the absolute number of men affected by osteoporosis and fractures is large, as at least 2.8 million men in the United States are thought to have osteoporosis. Questions/purposes The purposes of this review are to (1) highlight gender differences in osteoporosis and fracture risk, (2) describe disparities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
153
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(172 citation statements)
references
References 37 publications
12
153
0
3
Order By: Relevance
“…Similar findings were noted in previous concomitant upper limbs fracture studies; [5][6][7][8] this is consistent with higher fracture rates in elderly women due to the higher prevalence of osteoporosis. 24 Our study has inherent limitations of being a retrospective cohort study based on ICD-10 coding. Limitations include variability in electronic and written records, coder's trainingand experience and coder's error (such as misspecification, unbundling and upcoding).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were noted in previous concomitant upper limbs fracture studies; [5][6][7][8] this is consistent with higher fracture rates in elderly women due to the higher prevalence of osteoporosis. 24 Our study has inherent limitations of being a retrospective cohort study based on ICD-10 coding. Limitations include variability in electronic and written records, coder's trainingand experience and coder's error (such as misspecification, unbundling and upcoding).…”
Section: Discussionmentioning
confidence: 99%
“…This might be because osteoporosis is generally thought of as a "woman's disease." The prevalence of osteoporosis and the rate of fractures are much higher in postmenopausal women than in older man (Cawthon 2011). Moreover, men tend to have worse outcomes after fracture (Cawthon 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of osteoporosis and the rate of fractures are much higher in postmenopausal women than in older man (Cawthon 2011). Moreover, men tend to have worse outcomes after fracture (Cawthon 2011). Thus, this could lead to investigate further by requesting an MRI after a lumbosacral spine X-ray.…”
Section: Discussionmentioning
confidence: 99%
“…From the 10 million residents of Hungary, it is estimated that in the population over 50 years of age 547,107 people suffered from osteoporosis, of which 94,949 were males and 452,158 were females in 2010 [22,23]. Similar prevalence rates were found in the European Union, while the rate was higher in the U.S.A. [18,22,23]. Amongst fall-related low-energy bone fractures, hip fractures are the most significant consequences of osteoporosis: they put a huge financial burden on the health care system and on the patients as well, besides extreme pain and high morbidity and mortality rates.…”
Section: Figurementioning
confidence: 78%
“…Other than medication use, many studies have revealed a variety of factors or conditions that can increase the risk of falling in elderly patients, such as older age, comorbidities, vitamin D deficiency, vision disturbances, diabetes, depression and osteoporosis [6,8,18]. In the present thesis, osteoporosis and serum vitamin D level have been studied as risk factors for falls (and fractures).…”
Section: Introductionmentioning
confidence: 92%